Thermal Effects on the MIG-SMD Parts Characteristics: A Review (Eurasian Journal of Engineering and Technology, 2022)
Shaped metal deposition (SMD) is a revolutionary process for fabricating near-netshaped products by consecutive layer deposition with the aid of a welding machine. The SMD rig comprises a robot and a manipulator equipped with an inert gas welding torch. The SMD-fabricated object is frequently exposed to extreme temperature variations and rapid heating and cooling throughout the manufacturing process, resulting in a unique microstructure and morphology not seen with traditional production processes. Among the fundamental research, there are efforts to understand thermal behavior, which is a critical component of complex systems, and its effect on product quality. This paper intends to review the many ways to study the thermal impact on the final product